The plot against America. (Economist, 2016)
The article highlights the response of the U.S. government to Russia's efforts to influence the November 2016 presidential election, and shows how partisan division has weakened the U.S. economy. Topics discussed include the hacking of the Democratic National Committee's computer systems by two groups of hackers with known links to Russian intelligence, the Republicans' dismissal of claims that Russia tried to meddle in the election, and the Democratic leaders' response to the issue.